Association between neonatal malnutrition and bronchopulmonary dysplasia in very low‐birth‐weight infants: A propensity score–matched analysis. (16th February 2022) - Jiang, Honghua; Lv, Yuan; Hou, Weiwei; Xu, Xiang; Zhu, LingLing; Zhang, Hao; Shu, Guihua
Abstract: Objective: To investigate the relationship between the nutrition status of infants with bronchopulmonary dysplasia (BPD) at the first 4 weeks of life and the likelihood of developing neonatal malnutrition. Methods: A total of 1064 infants were divided into a BPD group and a non‐BPD group. After propensity score matching, there were 282 infants in each group. Infants were further divided into a neonatal malnutrition （NM） group and a well‐nourished （WN） group. Clinical factors, nutrition intake, and growth parameters were collected and analyzed. Multivariate logistic regression model was used to determine the factors associated with neonatal malnutrition. Results: 1. Compared with infants in the non‐BPD group, the infants in BPD group had more fluid intake and lower calorie and protein intake after the second week, longer invasive ventilation time, and longer time to total oral feeding and parenteral nutrition (PN), and the difference was more significant in NM infants than in WN infants ( P < 0.05). 2. The weight/length, body mass index, triponderal mass index, and weight gain velocity in the BPD group were significantly lower than in the non‐BPD group ( P < 0.05) and lower in NM infants than in WN ones ( P < 0.05). 3. Multivariable system regression analysis showed that invasive ventilation time, lipid intake in week 4, time to reach full feeding, and duration of PN were independent risk factors for NM. Conclusion: Enhancing calorie and macronutrient intake, reducing invasive ventilation, and achieving full gastrointestinal feeding early may be effective measures to avoid malnutrition in infants with BPD.